DEVICE CLOSURE OF ATRIAL SEPTAL DEFECT WITH AMPLATZER SEPTAL OCCLUDER IN ADULTS- SAFETY AND OUTCOME - Khan, Zahoor Aslam; Arif, Raja Adnan; ullah, Maad; Sultan, Mehboob (Journal of Ayub Medical College Abbottabad, 2013)
Background:Secundum atrial septal defect is a common congenital heart disease. Amplatzer septal occluder has become the most commonly used device for its closure. This study was conducted to determine the safety and outcome of atrial septal defect closure with the Amplatzer septal occlude (ASO). Methods: This Case-series was conducted at Armed Forces Institute of Cardiology/National Institute of Heart Diseases Rawalpindi from July 2010-11, on a total of 41 patients, out of these 41 patients, 18 (44%) patients underwent general anaesthesia while 23 (56%) patients were given local anaesthesia for the procedure. Trans-esophageal echocardiogram was done in all patients before procedure. Results:In 37 patients, ASD device closure was successfully done and size of ASD devices were 14-36 mm. Trans-oesophageal echocardiography guided ASD Device closure was done in 16 patients and rest of them done under transthoracic echocardiography. Size of ASD ranged from 11-36 mm (mean 22 mm). Mean floro time was 10 minutes. Four (10%) patients did not undergo the procedure due to inadequate rim. Conclusion: Device closure of Atrial Septal Defect with amplatzer septal occluder is convenient and safe. Keywords: Atrial septal defect, amplatzer septal occluder, patent foramen ovale